Meningkatkan Kerukunan Warga NU di Parengan Dengan Konsep Tasamuh Ahlussunnah Wal Jama’ah An-Nahdliyah - Jelieta Mutiarani; Kadi; Muhammad Nabhani (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
Tasamuh is an important attitude to apply in social life because it can minimize conflict and thus create a harmonious society. The aim of this research is to describe the phenomenon of implementing the concept of Tasamuh Ahlussunnah Wal Jama'ah An-Nahdliyah in increasing harmony in the NU community in Parengan Village and to describe the supporting and inhibiting factors in its implementation. This research uses a qualitative approach and is included in the type of field research. Data collection was carried out using observation, interviews, and documentation methods. The results of this research show that: 1) The implementation of the Tasamuh concept in Parengan Village is that the community has carried out its obligations and has accepted its rights well, accepts all existing differences, understands each other, gives freedom to others, needs to increase equality, namely treating people others equally without discrimination, and need to increase cooperation. 2) Supporting factors in implementing the values ​​of Tasamuh Aswaja An-Nahdliyah in Parengan Village are that religious leaders carry out their roles well, family and kinship relationships in the community are well established, and good cooperation in the community. Meanwhile, the inhibiting factor is that the village government has not carried out its role optimally, especially in the field of cooperation.